Strategy and business process management : techniques for improving execution, adaptability, and consistency - Lehmann, Carl F. (CRC Press, 2012)
"This book prepares readers to master an IT and managerial discipline quickly gaining momentum in organizations of all sizes--Business Process Management (BPM). It describes how BPM treats processes as a portfolio of strategic assets that create and deliver customer and shareholder value and adapt, when necessary, enabling competitive advantage through consistent performance. Strategy and Business Process Management: Techniques for Improving Execution, Adaptability, and Consistency defines the planning framework and managerial mindset necessary to craft and drive highly effective business process improvement projects and continuous improvement programs. Readers will learn specific techniques used by industry leaders to formulate and execute business strategy that adapts organizational behavior, business processes and information technology as a dynamic system designed to assure consistent performance and achievement, even when challenged with unexpected change or opportunity"-- Vydavatelská anotace
Keywords: strategický management; strategic planning; monografie; monographs